Copper surface coarsening liquid, preparation method thereof and application of copper surface coarsening liquid in circuit board resistance welding pretreatment
By using modified chitosan and polylysine in the copper surface roughening liquid to form an organic layer, combining palladium ions and zinc ions as a promoter, the problem of poor coarse effect of traditional copper surface roughening liquid is solved, and the problem of poor coarsing effect is achieved. Higher roughness and bond strength and maintain good storage performance.
Patent Information
- Application Number
- CN202411231111.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2025-01-10
AI Technical Summary
Traditional copper surface roughening liquid is difficult to achieve the required performance indicators in some application scenarios with high requirements for roughness and surface area, and the roughening effect is not ideal.
Using a copper surface roughening solution containing modified chitosan and polylysine, an organic layer is formed by reacting modified chitosan with ethylenediamine and glutaraldehyde to increase the corrosion pit on the copper surface, combining palladium ions and Zinc ions act as a promoter to adjust the pH value to improve surface roughness and coarse uniformity.
It significantly improves the roughness of the copper surface and the adhesion strength and consistency of the electroplating layer, enhances the bonding force between the copper surface and the solder shield ink, and has good storage performance.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of printed circuit boards, and in particular to a copper surface roughening liquid and a preparation method thereof, and an application thereof in the pre-treatment of solder resist of circuit boards. Background Art
[0002] Copper surface roughening liquid is a chemical agent specially used to treat copper surface. It is widely used in electronics, semiconductors and printed circuit boards. By using copper surface roughening liquid to treat copper surface, the roughness of copper surface can be effectively improved, which is beneficial to improve the bonding strength between copper surface and other materials and prevent peeling or delamination. In addition, roughening treatment can also improve the uniformity and consistency of electroplating layer when electroplating on copper surface and reduce the occurrence of defects.
[0003] Traditional copper surface roughening liquid is mainly based on strong acid or strong oxidant, such as nitric acid, hydrochloric acid, sulfuric acid or hydrogen peroxide, which oxidizes or dissolves tiny particles on the copper surface to form irregular microstructures and increase surface roughness. In actual operation, the copper sheet to be roughened often needs to be cleaned and decontaminated before being immersed in the roughening liquid for roughening treatment. However, the roughening effect of traditional copper surface roughening liquid is often not ideal. In some application scenarios with high requirements for roughness and surface area, traditional roughening liquid is difficult to achieve the required performance indicators. Therefore, it is urgent to provide a solution to improve the above solution. Summary of the invention
[0004] The purpose of the present invention is to provide a copper surface roughening liquid and a preparation method and application thereof.
[0005] In a first aspect, the present invention provides a copper surface roughening solution, which comprises, by mass concentration: 30-50 g / L copper ions, 40-60 g / L chloride ions, 4-6 g / L roughening agent and 2-3 g / L promoter; the roughening agent comprises modified chitosan and polylysine, and the promoter comprises at least one of palladium ions and zinc ions; the preparation method of the modified chitosan comprises: dissolving chitosan and ethylenediamine in a glutaraldehyde solution, stirring the reaction and separating to obtain the modified chitosan; and also comprises an organic acid for maintaining the pH value of the roughening solution at 4.5-6.
[0006] The copper surface roughening liquid provided by the present invention can form an organic layer on the copper surface by adding modified chitosan and polylysine, which is helpful to form fine corrosion pits on the copper surface and can effectively increase the surface roughness. In addition, during the roughening treatment process, more amino groups are introduced into chitosan, which can effectively improve the interaction between chitosan and copper ions, thereby promoting surface corrosion of the copper surface through coordination. At the same time, polylysine can form a stable complex with the copper surface and adhere to the copper surface.
[0007] Optionally, the preparation method of the modified chitosan comprises: mixing ethylenediamine and chitosan acetic acid solution at 30-35°C to obtain a primary reaction solution; adding glutaraldehyde solution dropwise into the reaction solution to obtain a secondary reaction solution; adding anhydrous ethanol to the secondary reaction solution, separating and precipitating, and drying to obtain the modified chitosan.
[0008] Optionally, the mass fraction of chitosan in the chitosan acetic acid solution is 1-3%.
[0009] Optionally, the mass ratio of the ethylenediamine to the chitosan in the chitosan acetic acid solution is (0.8-1.2):1.
[0010] Optionally, the mass ratio of glutaraldehyde in the glutaraldehyde solution to chitosan in the chitosan acetic acid solution is (0.2-0.3):1.
[0011] Alternatively, the glutaraldehyde solution is added dropwise to the reaction solution within 30-40 min.
[0012] Optionally, when anhydrous ethanol is added to the secondary reaction liquid, the volume ratio of the secondary reaction liquid to the anhydrous ethanol is 1:(8-10).
[0013] Optionally, separation of the precipitate includes at least one of filtration separation, suction filtration separation and dialysis separation.
[0014] Optionally, the precipitate is separated and then rinsed with deionized water and anhydrous ethanol.
[0015] Optionally, the precipitate is separated and dried under vacuum at 50-60°C.
[0016] Optionally, the chitosan acetic acid solution is kept at 30-35° C. for 1-2 hours, and then ethylenediamine is added dropwise to the chitosan acetic acid solution within 10-15 minutes, and mixed and reacted for 1-2 hours to obtain a primary reaction solution.
[0017] Optionally, the roughening agent comprises modified chitosan and polylysine in a mass ratio of 1:(0.3-0.5).
[0018] Optionally, the promoter comprises palladium ions and zinc ions in a molar ratio of 1:(0.8-1.2).
[0019] Optionally, the organic acid includes at least one of formic acid, propionic acid and butyric acid.
[0020] Optionally, the source of the copper ions includes at least one of copper sulfate, copper chloride and copper nitrate.
[0021] Optionally, the source of the chloride ions includes at least one of sodium chloride, copper chloride and zinc chloride.
[0022] Optionally, the source of the palladium ions includes at least one of palladium chloride and palladium nitrate.
[0023] Optionally, the source of zinc ions includes at least one of zinc sulfate, zinc nitrate and zinc chloride.
[0024] In a second aspect, the present invention provides a method for preparing any of the above-mentioned optional copper surface roughening solutions, comprising the following steps: stirring and dissolving a roughening agent and a promoter in a mixed solution of copper ions and chloride ions to obtain a precursor solution; adding an organic acid to the precursor solution to adjust the pH to 4.5-6 to obtain a copper surface roughening solution.
[0025] In a third aspect, the present invention also provides an application of a copper surface roughening liquid in the pre-treatment of solder mask of a circuit board. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meanings understood by people with general skills in the field to which the present invention belongs.
[0027] The present invention provides a copper surface roughening solution, which includes 30-50 g / L copper ions, 40-60 g / L chloride ions, 4-6 g / L roughening agent and 2-3 g / L accelerator in terms of mass concentration. In fact, the copper surface roughening solution also includes an organic acid, wherein the organic acid is used to maintain the pH of the copper surface roughening solution at 4.5-6.
[0028] In fact, copper ions as the main component in the copper surface roughening solution promote the dissolution of copper surface molecules and surface roughening through redox reactions. Therefore, the concentration of copper ions will directly affect the roughening rate and the final roughening effect. When the copper ion concentration is too high, the reaction rate is too fast, which can easily lead to excessive roughness of the copper surface and uneven roughness. When the copper ion concentration is too low, the reaction rate is too slow, which seriously affects the roughening efficiency.
[0029] In fact, in the copper surface roughening solution, chloride ions can enhance the oxidation effect on the copper surface and form copper-chloride complexes with copper, which can not only effectively control the copper ion concentration, but also avoid excessive deposition of copper ions. At the same time, chloride ions can also corrode the copper surface to a certain extent, thereby further enhancing the roughening effect. In addition, the dispersion of copper-chloride complexes in the roughening solution helps to improve the uniformity and stability of the roughening degree.
[0030] In some embodiments, the roughening solution includes modified chitosan and polylysine. In fact, the modified chitosan is modified by introducing more amino groups into the natural polysaccharide chitosan, which can significantly improve the complexation of copper ions. When the modified chitosan comes into contact with the copper surface, it can form a coordination bond with copper, thereby locally changing the electrochemical environment of the copper surface, thereby promoting the corrosion and roughening efficiency of copper. Polylysine is a linear polypeptide rich in amino groups, which can also form a stable coordination complex with copper, which can not only effectively improve the stability of the concentration of copper ions in the roughening solution, but also prevent excessive deposition of copper ions on the copper surface.
[0031] Specifically, the preparation method of modified chitosan comprises: dissolving chitosan and ethylenediamine in a glutaraldehyde solution, stirring and reacting, and then separating the modified chitosan. By reacting chitosan and ethylenediamine under the action of glutaraldehyde as a crosslinking agent to introduce more amino groups on the surface of chitosan, the surface amino amount of chitosan can be effectively increased, thereby improving the roughening effect of the roughening solution on the copper surface.
[0032] In some embodiments, the preparation method of modified chitosan specifically includes:
[0033] S1, mixing ethylenediamine and chitosan acetic acid solution at 30-35° C. to prepare a primary reaction solution;
[0034] S2, adding the glutaraldehyde solution dropwise into the primary reaction solution for mixed reaction to obtain a secondary reaction solution;
[0035] S3. Adding anhydrous ethanol into the secondary reaction solution, separating the precipitate and drying it to obtain modified chitosan.
[0036] In fact, during the execution of step S1, ethylenediamine can be introduced into the chitosan molecular chain, thereby effectively increasing the amino content in the chitosan. This is because ethylenediamine is an organic compound with a diamino group, which enters the chitosan molecular chain by reacting with chitosan.
[0037] In fact, in the process of executing step S1, by using chitosan acetic acid solution, not only the solubility of chitosan can be improved, but also the reaction of ethylenediamine and chitosan can be placed in a weakly acidic environment. In the acidic environment, the amino groups in chitosan are protonated and become more reactive, so that they can undergo a cross-linking reaction with ethylenediamine to form a longer amino chain.
[0038] In some embodiments, during the execution of step S1, the mass fraction of chitosan in the chitosan acetic acid solution is 1-3%, and the mass ratio of ethylenediamine to chitosan is (0.8-1.2): 1. In fact, by controlling the amount of ethylenediamine and chitosan, the components in the primary reaction liquid after the reaction of ethylenediamine and chitosan can be effectively controlled, thereby increasing the concentration of the initial modified substance formed after the reaction of ethylenediamine and chitosan.
[0039] In some embodiments, during the execution of step S1, the chitosan acetic acid solution is kept at 30-35°C for 1-2 hours, and then ethylenediamine is added dropwise to the chitosan acetic acid solution within 10-15 minutes, and mixed and reacted for 1-2 hours to obtain a primary reaction solution. In fact, by keeping the chitosan acetic acid solution at 30-35°C, the reaction activity of chitosan can be effectively improved, and then ethylenediamine is added dropwise to the chitosan acetic acid solution, which can effectively increase the reaction rate to generate the initial modified substance.
[0040] In some embodiments, during the execution of step S2, the mass ratio of glutaraldehyde to chitosan in the glutaraldehyde solution is (0.2-0.3):1, and the glutaraldehyde solution is specifically added dropwise to the primary reaction solution within 30-40 minutes. In fact, by adding the glutaraldehyde solution dropwise to the primary reaction solution, glutaraldehyde, as a dialdehyde compound, can react with chitosan to form a Schiff base bond, thereby further cross-linking the chitosan molecules to form a stable network structure, which can effectively improve the effectiveness of the modified chitosan when stored in the roughening solution.
[0041] In some embodiments, when anhydrous ethanol is added to the secondary reaction liquid during step S3, the volume ratio of the secondary reaction liquid to the anhydrous ethanol is 1:(8-10). In fact, the addition of anhydrous ethanol can effectively reduce the solubility of the modified chitosan in the secondary reaction liquid, thereby facilitating the precipitation of the modified chitosan and facilitating the storage and use of the modified chitosan.
[0042] In some embodiments, during the process of performing step S3, the separation of the precipitate includes at least one of filtration separation, suction filtration separation and dialysis separation. In practice, after the separation of the precipitate, it is rinsed with deionized water and anhydrous ethanol and dried under a vacuum environment at 50-60°C.
[0043] In some embodiments, the roughening agent in the roughening solution includes modified chitosan and polylysine in a mass ratio of 1:(0.3-0.5).
[0044] In some embodiments, the promoter includes at least one of palladium ions and zinc ions. By promoting the catalytic effect of palladium ions and zinc ions in the roughening solution, the surface roughening reaction of the copper surface can be effectively improved, thereby improving the roughening effect. Specifically, the promoter includes palladium ions and zinc ions in a molar ratio of 1: (0.8-1.2).
[0045] Specifically, the organic acid in the roughening solution includes at least one of formic acid, propionic acid, and butyric acid, the source of copper ions includes at least one of copper sulfate, copper chloride, and copper nitrate, the source of chloride ions includes at least one of sodium chloride, copper chloride, and zinc chloride, the source of palladium ions includes at least one of palladium chloride and palladium nitrate, and the source of zinc ions includes at least one of zinc sulfate, zinc nitrate, and zinc chloride.
[0046] The present invention also provides a method for preparing the copper surface roughening solution in any of the above embodiments, comprising the following steps: stirring and dissolving a roughening agent and a promoter in a mixed solution of copper ions and chloride ions to obtain a precursor solution; adding an organic acid to the precursor solution to adjust the pH to 4.5-6 to obtain the copper surface roughening solution.
[0047] In fact, the copper surface roughening liquid provided by the present invention can be used in the pre-treatment of circuit board solder mask. By roughening the surface of the copper-based circuit board, the adhesion strength and consistency of the copper-based circuit board to the electroplating layer can be effectively improved.
[0048] Preparation Example 1
[0049] This preparation example 1 provides a method for preparing modified chitosan, comprising the following steps:
[0050] S1. Chitosan (CAS: 9012-76-4) was stirred and dissolved in glacial acetic acid to prepare a chitosan acetic acid solution with a mass fraction of 2%, and the chitosan acetic acid solution was kept at 33°C for 2 hours, and ethylenediamine (CAS: 107-15-3; the mass ratio of ethylenediamine to chitosan was 1:1) was added dropwise to the chitosan acetic acid solution within 10 minutes, and after ultrasonic blending, the mixture was stirred at a speed of 200 rpm for 2 hours to obtain a primary reaction solution;
[0051] S2, stirring and dissolving glutaraldehyde (CAS: 111-30-8; mass ratio of glutaraldehyde to chitosan is 0.2:1) in glacial acetic acid to prepare a glutaraldehyde solution, then adding the glutaraldehyde solution dropwise into the primary reaction solution within 35 minutes, ultrasonically blending, and stirring at a speed of 200 rpm for 1 hour to obtain a secondary reaction solution;
[0052] S3. Add 10 volumes of anhydrous ethanol to the secondary reaction solution, stir and mix, filter and separate, rinse the precipitate three times with anhydrous ethanol and deionized water, transfer the washed precipitate to a vacuum drying oven at 50° C. and dry to constant weight to obtain modified chitosan.
[0053] Preparation Example 2
[0054] This preparation example 2 provides a method for preparing modified chitosan, comprising the following steps:
[0055] S1. Chitosan (CAS: 9012-76-4) was stirred and dissolved in glacial acetic acid to prepare a chitosan acetic acid solution with a mass fraction of 2%, and the chitosan acetic acid solution was kept at 33°C for 2 hours, and ethylenediamine (CAS: 107-15-3; the mass ratio of ethylenediamine to chitosan was 1:1) was added dropwise to the chitosan acetic acid solution within 10 minutes, and after ultrasonic blending, the mixture was stirred at a speed of 200 rpm for 2 hours to obtain a primary reaction solution;
[0056] S2. Add 10 volumes of anhydrous ethanol to the primary reaction solution, stir and mix, filter and separate, rinse the precipitate three times with anhydrous ethanol and deionized water, transfer the washed precipitate to a vacuum drying oven at 50° C. and dry to constant weight to obtain modified chitosan.
[0057] Preparation Example 3
[0058] This preparation example 3 provides a method for preparing modified chitosan, comprising the following steps:
[0059] S1. Chitosan (CAS: 9012-76-4) was stirred and dissolved in glacial acetic acid to prepare a chitosan acetic acid solution with a mass fraction of 2%, glutaraldehyde (CAS: 111-30-8; the mass ratio of glutaraldehyde to chitosan was 0.2:1) was stirred and dissolved in glacial acetic acid to prepare a glutaraldehyde solution, and the chitosan acetic acid solution was kept at 33° C. for 2 h, and then the glutaraldehyde solution was added dropwise to the chitosan acetic acid solution within 35 min, and after ultrasonic blending, the mixture was stirred at a speed of 200 rpm for 1 h to obtain a primary reaction solution;
[0060] S2. Add 10 volumes of anhydrous ethanol to the primary reaction solution, stir and mix, filter and separate, rinse the precipitate three times with anhydrous ethanol and deionized water, transfer the washed precipitate to a vacuum drying oven at 50° C. and dry to constant weight to obtain modified chitosan.
[0061] Example 1
[0062] This embodiment 1 provides a method for preparing a copper surface roughening solution, comprising the following steps:
[0063] Y1. Dissolve copper sulfate in deionized water to prepare a copper ion solution, and dissolve sodium chloride in deionized water to prepare a chloride ion solution, and mix the copper ion solution and the chloride ion solution to prepare a mixed solution;
[0064] Y2, a roughening agent (modified chitosan (Preparation Example 1) and polylysine (purchased from Wuhan Huaxiang Kejie Biotechnology Co., Ltd.) in a mass ratio of 1:0.5) and an accelerator (palladium chloride) were mixed and dissolved in a mixed solution, and a precursor solution was obtained after ultrasonic blending at 30° C. for 30 minutes;
[0065] Y3. After adding formic acid to the precursor solution to adjust the pH to 5, keep it warm for 30 minutes and then adjust the volume to obtain a copper surface roughening solution; the solution includes 40g / L copper ions, 50g / L chloride ions, 5g roughening agent and 3g / L accelerator.
[0066] Example 2
[0067] This embodiment 2 provides a method for preparing a copper surface roughening solution, comprising the following steps:
[0068] Y1. Dissolve copper sulfate in deionized water to prepare a copper ion solution, and dissolve sodium chloride in deionized water to prepare a chloride ion solution, and mix the copper ion solution and the chloride ion solution to prepare a mixed solution;
[0069] Y2, a roughening agent (modified chitosan (Preparation Example 1) and polylysine (purchased from Wuhan Huaxiang Kejie Biotechnology Co., Ltd.) in a mass ratio of 1:0.5) and an accelerator (zinc chloride) were mixed and dissolved in a mixed solution, and a precursor solution was obtained after ultrasonic blending at 30° C. for 30 minutes;
[0070] Y3. After adding formic acid to the precursor solution to adjust the pH to 5, keep it warm for 30 minutes and then adjust the volume to obtain a copper surface roughening solution; the solution includes 40g / L copper ions, 50g / L chloride ions, 5g roughening agent and 3g / L accelerator.
[0071] This embodiment 3 provides a method for preparing a copper surface roughening solution, comprising the following steps:
[0072] Y1. Dissolve copper sulfate in deionized water to prepare a copper ion solution, and dissolve sodium chloride in deionized water to prepare a chloride ion solution, and mix the copper ion solution and the chloride ion solution to prepare a mixed solution;
[0073] Y2, a roughening agent (modified chitosan (Preparation Example 1) and polylysine (purchased from Wuhan Huaxiang Kejie Biotechnology Co., Ltd.) in a mass ratio of 1:0.5) and an accelerator (palladium chloride and zinc chloride in a molar ratio of 1:1) were mixed and dissolved in a mixed solution, and a precursor solution was obtained after ultrasonic blending at 30° C. for 30 minutes;
[0074] Y3. After adding formic acid to the precursor solution to adjust the pH to 5, keep it warm for 30 minutes and then adjust the volume to obtain a copper surface roughening solution; the solution includes 40g / L copper ions, 50g / L chloride ions, 5g roughening agent and 3g / L accelerator.
[0075] Comparative Example 1
[0076] This comparative example 1 provides a method for preparing a copper surface roughening solution, comprising the following steps:
[0077] D1. Dissolve copper sulfate in deionized water to prepare a copper ion solution, and dissolve sodium chloride in deionized water to prepare a chloride ion solution, and mix the copper ion solution and the chloride ion solution to prepare a mixed solution;
[0078] D2, a roughening agent (modified chitosan (Preparation Example 1) with a mass ratio of 1:0.5) and an accelerator (palladium chloride and zinc chloride with a molar ratio of 1:1) were mixed and dissolved in a mixed solution, and ultrasonically blended at 30° C. for 30 minutes to obtain a precursor solution;
[0079] D3. After adding formic acid to the precursor solution to adjust the pH to 5, keep it warm for 30 minutes and then adjust the volume to obtain a copper surface roughening solution; the solution includes 40g / L copper ions, 50g / L chloride ions, 5g roughening agent and 3g / L accelerator.
[0080] Comparative Example 2
[0081] This comparative example 2 provides a method for preparing a copper surface roughening solution, comprising the following steps:
[0082] D1. Dissolve copper sulfate in deionized water to prepare a copper ion solution, and dissolve sodium chloride in deionized water to prepare a chloride ion solution, and mix the copper ion solution and the chloride ion solution to prepare a mixed solution;
[0083] D2, a roughening agent (polylysine (purchased from Wuhan Huaxiang Kejie Biotechnology Co., Ltd.)) and an accelerator (palladium chloride and zinc chloride in a molar ratio of 1:1) were mixed and dissolved in a mixed solution, and ultrasonically blended at 30° C. for 30 minutes to obtain a precursor solution;
[0084] Y3. After adding formic acid to the precursor solution to adjust the pH to 5, keep it warm for 30 minutes and then adjust the volume to obtain a copper surface roughening solution; the solution includes 40g / L copper ions, 50g / L chloride ions, 5g roughening agent and 3g / L accelerator.
[0085] Comparative Example 3
[0086] This comparative example 3 provides a method for preparing a copper surface roughening solution, comprising the following steps:
[0087] D1. Dissolve copper sulfate in deionized water to prepare a copper ion solution, and dissolve sodium chloride in deionized water to prepare a chloride ion solution, and mix the copper ion solution and the chloride ion solution to prepare a mixed solution;
[0088] D2, mixing and dissolving the accelerator (palladium chloride and zinc chloride in a molar ratio of 1:1) in the mixed solution, and ultrasonically blending at 30° C. for 30 minutes to obtain a precursor solution;
[0089] Y3. After adding formic acid to the precursor solution to adjust the pH to 5, keep it warm for 30 minutes and then adjust the volume to obtain a copper surface roughening solution; the solution includes 40 g / L copper ions, 50 g / L chloride ions and 3 g / L accelerator.
[0090] Comparative Example 4
[0091] This comparative example 4 provides a method for preparing a copper surface roughening solution, comprising the following steps:
[0092] D1. Dissolve copper sulfate in deionized water to prepare a copper ion solution, and dissolve sodium chloride in deionized water to prepare a chloride ion solution, and mix the copper ion solution and the chloride ion solution to prepare a mixed solution;
[0093] D2, a roughening agent (modified chitosan (Preparation Example 1) and polylysine (purchased from Wuhan Huaxiang Kejie Biotechnology Co., Ltd.) in a mass ratio of 1:0.5) were mixed and dissolved in the mixed solution, and ultrasonically blended at 30° C. for 30 minutes to obtain a precursor solution;
[0094] D3. After adding formic acid to the precursor solution to adjust the pH to 5, keep it warm for 30 minutes and then adjust the volume to obtain a copper surface roughening solution; the solution includes 40g / L copper ions, 50g / L chloride ions and 5g of a roughening agent.
[0095] Comparative Example 5
[0096] This comparative example 5 provides a method for preparing a copper surface roughening solution, comprising the following steps:
[0097] D1. Dissolve copper sulfate in deionized water to prepare a copper ion solution, and dissolve sodium chloride in deionized water to prepare a chloride ion solution, and mix the copper ion solution and the chloride ion solution to prepare a mixed solution;
[0098] D2, a roughening agent (modified chitosan (Preparation Example 2) and polylysine (purchased from Wuhan Huaxiang Kejie Biotechnology Co., Ltd.) in a mass ratio of 1:0.5) and an accelerator (palladium chloride and zinc chloride in a molar ratio of 1:1) were mixed and dissolved in a mixed solution, and ultrasonically blended at 30° C. for 30 minutes to obtain a precursor solution;
[0099] D3. After adding formic acid to the precursor solution to adjust the pH to 5, keep it warm for 30 minutes and then adjust the volume to obtain a copper surface roughening solution; the solution includes 40g / L copper ions, 50g / L chloride ions and 5g of a roughening agent.
[0100] Comparative Example 6
[0101] This comparative example 6 provides a method for preparing a copper surface roughening solution, comprising the following steps:
[0102] D1. Dissolve copper sulfate in deionized water to prepare a copper ion solution, and dissolve sodium chloride in deionized water to prepare a chloride ion solution, and mix the copper ion solution and the chloride ion solution to prepare a mixed solution;
[0103] D2, a roughening agent (modified chitosan (Preparation Example 3) and polylysine (purchased from Wuhan Huaxiang Kejie Biotechnology Co., Ltd.) in a mass ratio of 1:0.5) and an accelerator (palladium chloride and zinc chloride in a molar ratio of 1:1) were mixed and dissolved in a mixed solution, and ultrasonically blended at 30° C. for 30 minutes to obtain a precursor solution;
[0104] D3. After adding formic acid to the precursor solution to adjust the pH to 5, keep it warm for 30 minutes and then adjust the volume to obtain a copper surface roughening solution; the solution includes 40g / L copper ions, 50g / L chloride ions and 5g of a roughening agent.
[0105] Performance Testing
[0106] The copper surface roughening liquid prepared in Examples 1 to 3 and Comparative Examples 1 to 6 was used to roughen the surface of a copper-based circuit board, comprising the following steps: spraying the copper surface roughening liquid on the surface of the copper-based circuit board that had been pre-treated for surface rust removal and degreasing at 30° C., controlling the spraying time to 60 minutes and then washing with water, and testing the following items on the roughened copper-based circuit board:
[0107] 1. Peel strength test: After the roughening treatment, the surface of the copper-based circuit board was coated with a solder resist ink with a thickness of 20 μm and then cured for adhesion test. Three peel tests were performed on different areas of the same circuit board and the average value was taken. The results are shown in Table 1 below;
[0108] 2. Roughness test: The test was conducted using a laser confocal microscope VKX-1000 based on ISO25178-6-2010. The test was repeated three times and the average value was taken. The results are shown in Table 1 below;
[0109] 3. Storage performance test: After the copper surface roughening liquid is placed in a constant temperature environment of 40°C for 168 hours, the above test items are repeated, and the bonding force attenuation value and the roughness attenuation value are calculated. The results are shown in Table 1 below.
[0110] Table 1 Performance test data of copper surface roughening liquid
[0111] Binding force (N / mm) Roughness(μm) Binding force attenuation (%) Roughness attenuation (%) Example 1 2.84 4.26 1.21 0.86 Example 2 2.81 4.18 1.24 0.92 Example 3 2.93 4.39 1.17 0.88 Comparative Example 1 2.42 3.14 1.91 1.67 Comparative Example 2 2.13 2.86 3.77 3.61 Comparative Example 3 1.57 2.42 5.64 5.12 Comparative Example 4 1.88 2.53 1.25 0.90 Comparative Example 5 2.69 3.28 1.67 1.34 Comparative Example 6 2.58 3.04 1.76 1.42
[0112] After the copper surface is treated with the copper surface roughening liquid provided by Examples 1 to 3 of the present invention, the roughness of the copper surface can be effectively improved, thereby improving the bonding strength between the copper surface and the solder resist ink, and can effectively improve the performance of the copper-based circuit board after solder resist. In addition, the copper surface roughening liquid provided by the present invention also has good storage performance, and the bonding strength and roughness attenuation of the copper surface after storage are small, which can effectively improve the usability of the copper surface roughening liquid.
[0113] At the same time, it can be seen from Examples 1 to 3 that the use of palladium chloride and zinc chloride as promoters in Example 3 can effectively improve the roughening efficiency and roughening effect of the roughening agent and the copper-based surface, and can effectively improve the roughness and bonding strength.
[0114] It can be seen from Example 3 and Comparative Example 1 that in Comparative Example 1, the use of modified chitosan as a roughening agent alone can also roughen the copper surface, but the roughening effect is significantly lower than that of Example 3 in which modified chitosan and polylysine are reused. Similarly, the preservation performance is also reduced, which shows that polylysine can not only promote the roughening effect, but also improve the storage performance.
[0115] It can be seen from Comparative Examples 1 and 2 that in Comparative Example 2, the roughening effect and storage performance of polylysine alone as a roughening agent are significantly deteriorated compared to Comparative Example 1, which indicates that modified chitosan is the main effective ingredient in the roughening agent, and polylysine can promote the roughening of the copper surface by modified chitosan.
[0116] It can be seen from Example 3 and Comparative Examples 1 to 3 that when no roughening agent is added to the roughening solution, a certain roughening effect can also be achieved on the copper-based surface, but the roughening effect is obviously inferior to the example of adding any roughening component.
[0117] It can be seen from Example 1 and Comparative Example 4 that when no accelerator is added in Comparative Example 4, this will affect the roughening reaction rate of the roughening agent on the copper surface, thereby reducing the roughening degree of the copper surface by the roughening liquid within a fixed time, thereby affecting the bonding strength, but the absence of the accelerator has no obvious effect on the storage performance of the roughening liquid.
[0118] It can be seen from Example 3, Comparative Example 5 and Comparative Example 6 that the use of ethylenediamine-chitosan modifier alone in Comparative Example 5 and the use of glutaraldehyde-chitosan modifier alone in Comparative Example 6 both significantly affect the roughening effect of the roughening solution on the copper surface, which shows that the modification method of chitosan has an important influence on the roughening performance of the roughening solution.
[0119] Although the embodiments of the present invention are described in detail above, it is obvious to those skilled in the art that various modifications and variations can be made to these embodiments. However, it should be understood that such modifications and variations are within the scope and spirit of the present invention as described in the claims. Moreover, the present invention described herein may have other embodiments and may be implemented or realized in a variety of ways.
Claims
1. A copper surface roughening solution, characterized in that: The invention comprises, in terms of mass concentration, 30-50 g / L copper ions, 40-60 g / L chloride ions, 4-6 g / L roughening agent and 2-3 g / L accelerator; the roughening agent comprises modified chitosan and polylysine, and the accelerator comprises at least one of palladium ions and zinc ions; the preparation method of the modified chitosan comprises: dissolving chitosan and ethylenediamine in a glutaraldehyde solution, stirring the solution for reaction, and then separating the modified chitosan; and further comprising an organic acid for maintaining the pH value of the roughening solution at 4.5-6.
2. The copper surface roughening solution according to claim 1, characterized in that: The preparation method of the modified chitosan comprises: mixing ethylenediamine and chitosan acetic acid solution at 30-35°C to obtain a primary reaction solution; adding glutaraldehyde solution dropwise into the primary reaction solution to obtain a secondary reaction solution; adding anhydrous ethanol to the secondary reaction solution, separating and precipitating, and drying to obtain the modified chitosan.
3. The copper surface roughening solution according to claim 2, characterized in that: The mass fraction of chitosan in the chitosan acetic acid solution is 1-3%; and / or, the mass ratio of ethylenediamine to chitosan in the chitosan acetic acid solution is (0.8-1.2):1; and / or, the mass ratio of glutaraldehyde in the glutaraldehyde solution to chitosan in the chitosan acetic acid solution is (0.2-0.3):
1.
4. The copper surface roughening solution according to claim 2, characterized in that: The glutaraldehyde solution is added dropwise to the primary reaction liquid within 30-40 minutes; and / or, when anhydrous ethanol is added to the secondary reaction liquid, the volume ratio of the secondary reaction liquid to the anhydrous ethanol is 1:(8-10); and / or, separation of the precipitate includes at least one of filtration separation, suction filtration separation and dialysis separation; and / or, after separation of the precipitate, it is rinsed with deionized water and anhydrous ethanol; and / or, after separation of the precipitate, it is dried under a vacuum environment of 50-60°C.
5. The copper surface roughening solution according to claim 2, characterized in that: After the chitosan acetic acid solution is kept at 30-35° C. for 1-2 hours, ethylenediamine is added dropwise into the chitosan acetic acid solution within 10-15 minutes, and mixed and reacted for 1-2 hours to obtain a primary reaction solution.
6. The copper surface roughening solution according to claim 1, characterized in that: The roughening agent comprises modified chitosan and polylysine in a mass ratio of 1:(0.3-0.5); and / or the accelerator comprises palladium ions and zinc ions in a molar ratio of 1:(0.8-1.2).
7. The copper surface roughening solution according to claim 1, characterized in that: The organic acid includes at least one of formic acid, propionic acid, and butyric acid; and / or the source of the copper ions includes at least one of copper sulfate, copper chloride, and copper nitrate; and / or the source of the chloride ions includes at least one of sodium chloride, copper chloride, and zinc chloride.
8. The copper surface roughening solution according to claim 1, characterized in that: The source of the palladium ions includes at least one of palladium chloride and palladium nitrate; and / or the source of the zinc ions includes at least one of zinc sulfate, zinc nitrate and zinc chloride.
9. A method for preparing the copper surface roughening solution according to any one of claims 1 to 8, characterized in that: The following steps are involved: The roughening agent and the accelerator are stirred and dissolved in a mixed solution of copper ions and chloride ions to prepare a precursor solution; Organic acid is added into the precursor solution to adjust the pH to 4.5-6 to obtain a copper surface roughening solution.
10. Use of the copper surface roughening solution as claimed in any one of claims 1 to 8 in the pre-treatment of solder mask on circuit boards.